Personalization of interactive news through J2EE, XML, XSLT, and SMIL in a Web-based multimedia content management system - Cheong,, S; Hanmandlu, , M; Azhar,, KM (2002)
This paper describes the design and implementation of a 5 layered web-based multimedia content management system (MCMS) using the Java 2 Enterprise Edition (J2EE). A prototype based on our framework has been implemented in the News On Demand KIOSK Network for organizing, integrating and composing of personalized digital news for interactive broadcasting. The aim of the MCMS project is to provide a collaborative environment among news producers for making them work more effectively despite the time and location constraints. The MCMS generates SMIL document that is structured, profiled and streamed to end-user using XML and XSLT techniques, which form the backbone of digital news broadcasting. The major contributions with regard to the digital MCMS can be summarized as: (1) Support for effective personalization of multimedia news content and presentation styles through the utilization of XML and XSLT. (2) Separation of design and content facilitated by MCMS. This allows journalist and editors to focus on content preparation rather than advanced HTML and SMIL coding. (3) Support for the re-use and re-purpose operations of the same multimedia elements to be part of the other digital news program. (4) Platform independent MCMS allowing an author to access the application everywhere via Internet without any need of additional hardware or software.